THE DYNAMICS OF MADRASAH IBTIDAIYAH IN IMPROVING THE QUALITY OF ISLAMIC EDUCATION IN INDONESIA - Bahri, Syaiful; Rais , Wendi; Rifa’I , Ahmad; Syamsuri, Syamsuri; Andari , AA (Fakultas Tarbiyah, IAIN Fattahul Muluk Papua, 2025)
This research analyses the application of various approaches in the learning process in Madrasah Ibtidaiyah (MI) in Indonesia, with a focus on improving the quality of Islamic education at the primary level. Using the Systematic Literature Review (SLR) method, this study collects, analyses and integrates research results related to the application of effective teaching methods and their impact on the quality of student learning outcomes. The main findings of this study show that activity-based approaches and real-life experiences, as well as the integration of technology in learning, can improve students' motivation and understanding of Islamic subject matter. The use of interactive learning media and e-learning provides a space for students to learn flexibly and in-depth, as well as assisting teachers in delivering materials in a more interesting and understandable way. In addition, this research also highlights the importance of the teacher's role in applying effective methods. Teachers with good pedagogic competence can create a conducive learning atmosphere, which has a positive impact on the quality of education. The involvement of parents and the community was also found to have a major effect on the quality of education in Madrasah Ibtidaiyah, by supporting students' character development. However, despite the successes, this study found challenges related to limited facilities and infrastructure, especially in rural areas, which hinder the implementation of innovative methods. In conclusion, this study illustrates that student-centred approaches, teachers' professional development and parents' and communities' involvement are crucial to improving the quality of Islamic education in Madrasah Ibtidaiyah, although challenges such as limited distribution of resources and facilities are still major obstacles that need to be overcome.